Bad Religion? Religion, Collective Action, and the Onset of Armed Conflict in Developing Countries. (March 2016) - Basedau, Matthias; Pfeiffer, Birte; Vüllers, Johannes
Anecdotal evidence from many armed conflicts suggests that religion incites violence. Theoretically speaking, several facets of religion can create motives and opportunities to overcome the collective action problems associated with organized violence. However, empirical research has hitherto found no conclusive answer on the extent to which religion is connected to armed conflict onset. Contributing to the filling of this gap, we use a new database that incorporates important religious factors that previous studies left largely untested. The data set covers 130 developing countries for the period 1990 to 2010. Results from logistic regressions confirm our expectation that certain religious factors fuel armed conflict—in particular, the overlap of religious and other identities, religious groups' grievances, and religious leaders' calls for violence. We also find that religious determinants vary in their impact according to whether conflicts are religious or not in origin.